Beta2-Adrenergic Receptor Polymorphisms and Haplotypes Associate With Chronic Pain in Sickle Cell Disease - Ellie H. Jhun; Nilanjana Sadhu; Xiaoyu Hu; Yingwei Yao; Yingwei Yao; Ying He; Ying He; Diana J. Wilkie; Diana J. Wilkie; Robert E. Molokie; Robert E. Molokie; Robert E. Molokie; et al. (Frontiers Media S.A., 2019)
Pain in sickle cell disease (SCD) is severe, variable, and inadequately comprehended. The β2-adrenergic receptor (ADRB2) is critical in mediating neurotransmitter response in the sympathetic nervous system. In this association study, we examined 16 single nucleotide polymorphisms (SNPs) covering 5'-UTR and coding regions of ADRB2 for pain variability in SCD. Subjects recorded their non-crisis, baseline pain experience on a computerized tool from which we obtained chronic pain measurement score- composite pain index (CPI). Regression models yielded significant associations between chronic pain and seven SNPs. Non-synonymous SNP rs1042713 A allele (Arg16) caused a 5.73-fold decrease in CPI (p = 0.002). Allele A of rs12654778 and T of rs17778257 reduced CPI by a fold of 4.52 (p = 0.019), and 4.39 (p = 0.032), respectively. Whereas, in the 5' UTR, allele C of rs1042711, G of rs11168070, C of rs11959427, and C of rs1801704 increased CPI by a fold of 10.86 (p = 0.00049), 5.99 (p = 0.016), 5.69 (p = 0.023), and 5.26 (p = 0.031), respectively. Together, these SNPs accounted for 2-15% of CPI variance after adjusting for covariates. Moreover, these SNPs were in high linkage disequilibrium (LD) showing three LD blocks in our cohort. A 10-marker haplotype increased CPI by 11.5-fold (p = 0.000407). Thus, ADRB2 polymorphisms might contribute to chronic pain severity and heterogeneity in SCD.